Entrepreneurship in regions: differentiated impacts of the socio cultural and gender types - Claudio Mancilla; AMOROS ESPINOZA, JOSÉ ERNESTO (My University, 2015)
PurposeThe purpose of this paper is to study the differentiated impact of factors that influence the propensity to entrepreneur in a sample of people in Chile. A distinction is made between individuals that live in primary cities and secondary cities. The differentiating factors are socio‐cultural aspects (reference models – positive examples of entrepreneurs – and perception of social fear of failure) and the gender of the individual.Design/methodology/approachFor the research data from the survey used in Chile by the Global Entrepreneurship Monitor for the years 2010 and 2011 were used. A logit model was used to determine the differentiated impact of the analysed factors and interactions were done using the method proposed by Corneliâen and Sonderhof (2009).FindingsThese showed that the fact that an individual lives in a secondary city decreases his entrepreneurship probability. The positive impact that the reference models have is weaker in women. Contrary to what was expected, the negative impact of the fear of failure perception is weaker in women.Practical implicationsThese results have the implications to suggest focused public policies and differentiations that consider the socio‐cultural, territorial (focused in cities) and gender aspects.Originality/valueThe research contributes by giving empirical evidence of the existence of the negative impact of living in a secondary city and of differentiated effects of socio‐cultural factors from the gender perspective.
Keywords: secondary cities; entrepreneurship; socio-cultural factors; differentiated impacts; women; regions